2001
DOI: 10.1023/a:1012502412612
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a New Plant Endopeptidase Isolated from Latex of Asclepias fruticosa L. (Asclepiadaceae)

Abstract: Asclepias fruticosa L. is a small shrub containing latex with proteolytic activity. The crude extract (latex diluted 1:250 and ultracentrifuged) contained 276 microg of protein/mL and the proteolytic activity reached 1.2 caseinolytic U/mL. This enzyme preparation was very stable even after 2 hours at 45 degrees C, but was quickly inactivated after 5 minutes at 80 degrees C. Chromatographic purification was achieved by FPLC using a cation exchanger (SP-Sepharose FF). Thus, a unique proteolitically active fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…Isoelectric focusing and zymogram evidenced the basic characteristic of funastrain c II (pI higher than 9.3; Fig. 4), in agreement with those obtained for other peptidases from the Asclepiadaceae family latex (Trejo et al, 2001).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Isoelectric focusing and zymogram evidenced the basic characteristic of funastrain c II (pI higher than 9.3; Fig. 4), in agreement with those obtained for other peptidases from the Asclepiadaceae family latex (Trejo et al, 2001).…”
Section: Resultssupporting
confidence: 87%
“…The knowledge of such parameters as optimum pH and PFLNA, L-pyroglutamyl-L-phenylalanyl-L-leucine-p-nitroanilide. Trejo et al, 2001Lynn et al, 1980Lynn et al, 1980Obregón et al, 2001Watanabe et al, 1991Koehler and Ho, 1990Koehler and Ho, 1990Conliffe et al, 1995Okamura et al, 1995Vairo et al, 2001Vairo et al, 2001Joseph et al, 1988Mitchell et al, 1970Dubois et al, 1988Portnoy et al, 1986 2). The N-CBZ-p-nitrophenyl ester derivative of Ala was chosen for the former determinations due to the high preference showed by the crude extract (unpublished).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of its potential applications, it is important to look into biochemical constituents of the Asclepiadaceae plant latex. In the course of screening of proteolytic enzymes of different species of the Asclepiadaceae family, our laboratory have reported the purification and characterization of proteases present in lattices of Morrenia brachystephana (Arri-be´re et al, 1998;Vairo Cavalli et al, 2001;Vairo Cavalli et al, 2003), M. odorata (Arribe´re et al, 1999;Vairo Cavalli et al, 2001), Araujia hortorum (Obregon et al, 2001;Priolo et al, 2000), and Asclepias fruticosa (Trejo et al, 2001). In the current paper we report the characterization of the crude extract obtained from latex of A. curassavica and the isolation and purification of the proteases present in it.…”
Section: Introductionmentioning
confidence: 99%
“…Pardo et al (2010), using casein as substrate, found that extracts form Asclepias fruticosa seeds exhibited a lower MCA/PA ratio (0.68) than the value reported in this study. In addition, proteases found in Jacaratia curumbensis (Arruda et al 2012), Lactuca sativa (Lo Piero et al 2002) and Asclepias fruticosa (Trejo et al 2001) and Onopordon acanthium (Brutti et al 2012), Cucumis melo (Uchikoba and Kaneda, 1996) and Zingiber officinale cv. Laiwu Shandong (Hashim et al 2011) possessed high caseinolytic activity in comparison with calf chymosin limiting their application for cheesemaking.…”
Section: Proteolytic Activity In B Pinguin Fruit Extractmentioning
confidence: 99%